2021
DOI: 10.3389/fchem.2021.744376
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Potencies of Phytochemicals Derived from Sesame Against SARS-CoV-2 Main Protease: A Molecular Docking and Simulation Study

Abstract: The ongoing COVID-19 pandemic, caused by SARS-CoV-2, has now spread across the nations with high mortality rates and multifaceted impact on human life. The proper treatment methods to overcome this contagious disease are still limited. The main protease enzyme (Mpro, also called 3CLpro) is essential for viral replication and has been considered as one of the potent drug targets for treating COVID-19. In this study, virtual screening was performed to find out the molecular interactions between 36 natural compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 125 publications
3
25
0
Order By: Relevance
“…The above finding may have just been verified by a recent in silico study using a computer-aided drug designing approach: Rifampicin was the most promising existing drug that could be repurposed for the treatment of COVID-19[ 39 ]. Moreover, using a comprehensive drug repurposing and molecular docking approach, prediction of potential inhibitors for RNA-dependent RNA polymerase of SARS-CoV-2 revealed that rifabutin could be an effective drug for COVID-19, having the lowest binding energy compared to the positive control remdesivir[ 40 ].…”
Section: In Silico Studies Indicate Possible Effectiveness O...mentioning
confidence: 83%
“…The above finding may have just been verified by a recent in silico study using a computer-aided drug designing approach: Rifampicin was the most promising existing drug that could be repurposed for the treatment of COVID-19[ 39 ]. Moreover, using a comprehensive drug repurposing and molecular docking approach, prediction of potential inhibitors for RNA-dependent RNA polymerase of SARS-CoV-2 revealed that rifabutin could be an effective drug for COVID-19, having the lowest binding energy compared to the positive control remdesivir[ 40 ].…”
Section: In Silico Studies Indicate Possible Effectiveness O...mentioning
confidence: 83%
“…The Open Babel toolbox ( O’Boyle et al, 2011 ) which is available in the PyRx package was utilized to convert these molecules into the PDBQT format. All four compounds were prepared by adding the polar hydrogens and Gasteiger charges as previously described in Kumar et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…Eleven amino acid residues, namely, Thr24, Thr26, Asn119, Phe140, Gly143, Cys145, His163, His164, Glu166, Gln189, and Thr190, were used as the active sites of the receptor protein. These active site residues were considered based on the previous reports by Khan et al (2020) and Kumar et al (2021) . During the molecular docking process, the M pro was fixed, while the ligand molecules were flexible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structure-based virtual screening (SBVS) of diverse ligand databases, many of them containing drug repurposing candidates and natural products, has been extensively applied to identify potential 3CL pro inhibitors (Wu C. et al, 2020;Chowdhury et al, 2020;Jukic et al, 2020;Meyer-Almes, 2020;Olubiyi et al, 2020;Selvaraj et al, 2020;Federico et al, 2021;Gogoi et al, 2021;Guedes et al, 2021;Kumar et al, 2021;Lokhande et al, 2021;Naik et al, 2021;Rajpoot et al, 2021;Rehman et al, 2021;Sisakht et al, 2021). In several cases, this approach has led to the successful identification of compounds displaying in vitro inhibitory activity against 3CL pro (Ghahremanpour et al, 2020;Gupta et al, 2020;Jin et al, 2020;Li et al, 2020;Alves et al, 2021;Banerjee et al, 2021;Gunther et al, 2021;Guo et al, 2021;Gupta et al, 2021;Hamdy et al, 2021;Pathak et al, 2021;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%